Monte Carlo 90Y PET/CT dosimetry of unexpected focal radiation-induced lung damage after hepatic radioembolisation. (24th November 2020) - Auditore, Lucrezia; Amato, Ernesto; Boughdad, Sarah; Meyer, Marie; Testart, Nathalie; Cicone, Francesco; Beigelman-Aubry, Catherine; Prior, John O; Schaefer, Niklaus; Gnesin, Silvano
Abstract: Transarterial radioembolization (TARE) with 90 Y-loaded microspheres is an established therapeutic option for inoperable hepatic tumors. Increasing knowledge regarding TARE hepatic dose-response and dose-toxicity correlation is available but few studies have investigated dose-toxicity correlation in extra-hepatic tissues. We investigated absorbed dose levels for the appearance of focal lung damage in a case of off-target deposition of 90 Y microspheres and compared them with the corresponding thresholds recommended to avoiding radiation induced lung injury following TARE. A 64-year-old male patient received 1.6 GBq of 90 Y-labelled glass microspheres for an inoperable left lobe hepatocellular carcinoma. A focal off-target accumulation of radiolabeled microspheres was detected in the left lung upper lobe at the post-treatment 90 Y-PET/CT, corresponding to a radiation-induced inflammatory lung lesion at the 3-months 18 F-FDG PET/CT follow-up. 90 Y-PET/CT data were used as input for Monte-Carlo based absorbed dose estimations. Dose-volume-histograms were computed to characterize the heterogeneity of absorbed dose distribution. The dose level associated with the appearance of lung tissue damage was estimated as the median absorbed dose measured at the edge of the inflammatory nodule. To account for respiratory movements and possible inaccuracy of image co-registration, three different methods were evaluated to define the irradiated off-target volume. Monte Carlo-derived absorbed dose distribution showed a highly heterogeneous absorbed dose pattern at the site of incidental microsphere deposition (volume = 2.13 ml) with a maximum dose of 630 Gy. Absorbed dose levels ranging from 119 Gy to 133 Gy, were estimated at the edge of the inflammatory nodule, depending on the procedure used to define the target volume. This report describes an original Monte Carlo based patient-specific dosimetry methodology for the study of the radiation-induced damage in a focal lung lesion after TARE. In our patient, radiation-induced focal lung damage occurred at significantly higher absorbed doses than those considered for single administration or cumulative lung dose delivered during TARE.